(untitled) (Edinburgh, 2003)
The transition from hospital medicine to primary health care presents many challenges for the GP Registrar and can be a daunting experience. The Successful GP Registrar's Companion will be your indispensable guide during that transition
Keywords: Family Practice,Education, Medical, Graduate; Education; Great Britain.,Great Britain